2003
DOI: 10.2320/matertrans.44.290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Under Bump Metallurgy and Reflows on Shear Strength and Microstructure of Joint between Cu Substrate and Sn-36Pb-2Ag Solder Alloy

Abstract: The interfacial reaction between Sn-36Pb-2Ag (numbers are all in mass% unless specified otherwise) solder balls and Ni, Ag and Ni/Ag electroplated on a Cu substrate was investigated and the joint bonding strength was measured using a ball shear tester. The intermetallic Ag 3 Sn was observed at the interface of the Cu/Ag/solder joint and Ni 3 Sn 4 was found at the Cu/Ni/solder joint. In the case of Cu/Ni/Ag substrate, the layer sequence was observed to be Cu/Ni/Ni 3 Sn 4 /Ag 3 Sn/solder. The Ag layer was comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…There are some reports on the correlation between growth of IMC and shear strength. They reported that the initial formation of the IMC at the interface means a good metallurgical bonding [17]- [19]. However, an overgrown IMC is known to be detrimental to the joint strength due to the brittle nature of IMCs.…”
Section: Die Shear Testmentioning
confidence: 99%
“…There are some reports on the correlation between growth of IMC and shear strength. They reported that the initial formation of the IMC at the interface means a good metallurgical bonding [17]- [19]. However, an overgrown IMC is known to be detrimental to the joint strength due to the brittle nature of IMCs.…”
Section: Die Shear Testmentioning
confidence: 99%
“…8 In order to study the interfacial reaction with diffusion at the interface, the solder-bumped samples were subjected to a thermal aging test at 250°C for 10, 20, and 30 min, respectively, in a N 2 atmosphere box oven in order to evaluate the UBM stability and solder bump integrity. The initial formation of the IMC at the interface indicates good metallurgical bonding.…”
Section: Thermal Agingmentioning
confidence: 99%